2019
DOI: 10.1093/brain/awz242
|View full text |Cite
|
Sign up to set email alerts
|

Recursive hierarchical embedding in vision is impaired by posterior middle temporal gyrus lesions

Abstract: Hierarchical structures are central to language, music and complex actions. Martins et al. demonstrate that the ability to represent visuospatial hierarchies shares cognitive and neural resources with the processing of linguistic syntax. Left posterior middle temporal gyrus lesions impair the integration of information during the generation of new hierarchical levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…We developed a new experimental paradigm consisting of two tasks which involved hierarchical (HIER) and iterative (ITER) processing. We confirmed behaviorally, that these new tasks correlated specifically with previously validated visuo-spatial recursive and iteration tasks (19, 54), thus showing that they are suitable for segregating hierarchical from non-hierarchy related processing. In fMRI we found that a left lateralized network encompassing lateral prefrontal and posterior temporal cortices was involved in the processing of hierarchies confirming previous studies in the domains of language and vision (5, 6, 19, 55).…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…We developed a new experimental paradigm consisting of two tasks which involved hierarchical (HIER) and iterative (ITER) processing. We confirmed behaviorally, that these new tasks correlated specifically with previously validated visuo-spatial recursive and iteration tasks (19, 54), thus showing that they are suitable for segregating hierarchical from non-hierarchy related processing. In fMRI we found that a left lateralized network encompassing lateral prefrontal and posterior temporal cortices was involved in the processing of hierarchies confirming previous studies in the domains of language and vision (5, 6, 19, 55).…”
Section: Discussionsupporting
confidence: 76%
“…We confirmed behaviorally, that these new tasks correlated specifically with previously validated visuo-spatial recursive and iteration tasks (19, 54), thus showing that they are suitable for segregating hierarchical from non-hierarchy related processing. In fMRI we found that a left lateralized network encompassing lateral prefrontal and posterior temporal cortices was involved in the processing of hierarchies confirming previous studies in the domains of language and vision (5, 6, 19, 55). We also confirmed previous findings demonstrating that IFG activity in the processing of hierarchical structures becomes stronger with increased automaticity (56, 57).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The roles of the pMTG in semantic retrieval, verbal memory, and multiple advanced network systems have been well documented in imaging (Davey et al, 2016;Karnath, 2001;Mesgarani, Cheung, Johnson, & Chang, 2014;Xu et al, 2015;Xu et al, 2019) and lesion (Leff et al, 2009;Martins et al, 2019) studies. Verbal learning and semantic retrieval are abstract cognitive functions in humans.…”
Section: A Path Potentially Mediating the Relationship Between Wmh And Recall Memorymentioning
confidence: 99%
“…In order to anticipate the environment in which it evolves, the cognitive system has to infer from the surface properties of the signal its underlying organization. The human brain is surprisingly good at this task and nested structure extraction has been demonstrated in multiple domains [1][2][3][4][5][6][7]. However, since the hierarchical structure is not present in the signal itself but must be inferred from it, the cognitive system cannot determine a priori if a signal has an underlying hierarchical organization [8,9].…”
Section: Introductionmentioning
confidence: 99%